Discourse, ideology and teaching in contemporaneity: the school as a place (and non-place) of urban and social interpretation - Leandro Siqueira Palcha; Odisséa Boaventura Oliveira (Universidade Federal de Santa Catarina, 2016)
This study analyzes six diaries of internship produced by undergraduates of a Biological Sciences course, in which they describe observations made on a Public School, intending to observe how ideological mechanisms faced at school emerge in the descriptions of these undergraduates. In the approximation of the School to the City, we analyze the relationship between the world of education and the reality of the subjects through the Discourse Analysis, in particular the concepts of Ideology, Urban Discourse and anthropological concepts of Place (space of relationship between identity, relational and historical) and Non-Place (illustrated by the relationship of distance). We observed that the students pointed out the school as in crisis of identity, relational and historical place - crisis in which the notions of place and non-place coexist in the same space at the same time. We emphasize that in the production of school knowledge and teachers education, we cannot think of practice, but of praxis (historical, dialogical and dialectical actions), and is necessary considers the school as a multifaceted space that produces discourses and ideologies, where the temporariness, conflicts, crises, pluralities and ruptures are intersected.     .